Understanding Human-Wildlife Interactions in Urban Environments: Im-plications for Conflicts, Disease Transmission, and Conservation - Ramadhan, Adam Lutfi (Law and Economics, 2024)
This research examines the effects of increased human-wildlife interactions on urban environments, focusing on the dynamics of conflicts and disease transmission. As urbanization continues to encroach upon natural habitats, interactions between humans and wildlife are becoming more frequent and complex, presenting challenges for urban planning, conservation, and public health. Through a comprehensive review of literature and case studies, this study identifies key challenges and limitations associated with managing human-wildlife interactions and proposes strategies to address them effectively. The research highlights the ecological, social, economic, and governance dimensions of human-wildlife interactions, emphasizing the need for interdisciplinary approaches that integrate ecological, social, and economic perspectives. Key findings include the importance of collaborative governance, adaptive management, community engagement, investment in research and monitoring, policy innovation, and public education in addressing human-wildlife interactions. This research contributes to a better understanding of the implications of human-wildlife interactions for urban planning and conservation, providing insights and recommendations for sustainable coexistence between humans and wildlife in urban environments.